1985
DOI: 10.1111/j.1469-185x.1985.tb00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Water‐regulatory Behaviour in Terrestrial Gastropods

Abstract: CONTENTSof the Linnean Society 53, 237-252. 31, 16-163. of Animal Ecology 13, 140-175. of Animal Ecology 14, 71-105. locomotor rhythm of Linax maximus. American Zoologist 16 (z), 219. rhythm of the garden slug, Limax. Journal of Experimental Zoology 216, 13-23. products. V. Humidity reactions. Journal of Experimental Biology 20, I 52-1 58.relation to the water content of the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 83 publications
2
57
0
1
Order By: Relevance
“…The effect of wood ash is similar to that of hydrated lime, as both substances cause dehydration of cuticle and blocking of airways (Boiteau et al, 2012). Prior (1985) reported that slugs are extremely susceptible to dehydration due to evaporative water loss across their integument and lung surface, and through deposition of their slime trail. It is surprising that diatomaceous earth in our experiment did not prove to be a substance which causes dehydration of slugs.…”
Section: Discussionmentioning
confidence: 79%
“…The effect of wood ash is similar to that of hydrated lime, as both substances cause dehydration of cuticle and blocking of airways (Boiteau et al, 2012). Prior (1985) reported that slugs are extremely susceptible to dehydration due to evaporative water loss across their integument and lung surface, and through deposition of their slime trail. It is surprising that diatomaceous earth in our experiment did not prove to be a substance which causes dehydration of slugs.…”
Section: Discussionmentioning
confidence: 79%
“…We and others (Prior 1984(Prior , 1985Banta et al 1990; Matanock and Welsford 1995) have observed Limax orient and move on a dry surface toward a source of water, prior to initiating contact rehydration. It is a mystery how an animal with a completely moist surface can show directed orientation to a localized source of water containing no explicit added odor cue, as dehydrated slugs are able to do.…”
Section: Providing Motivation For Learning Odor Associationsmentioning
confidence: 80%
“…Rapid dehydration produces maximally motivated slugs. Dehydrated slugs actively search for a source of water for contact rehydration (Prior 1985;Prior et al 1994;Matanock and Welsford 1995), which occurs when the slug sits on a moist surface and absorbs water through its foot via a paracellular pathway (Prior 1984;Prior and Uglem 1984;Banta et al 1990). During training, dehydrated slugs are first offered salt water containing quinine and NaCl for rehydration, paired with odor A.…”
Section: Providing Motivation For Learning Odor Associationsmentioning
confidence: 99%
“…Namestimo jih med mestom, kjer se polži skrivajo in mestom, kjer se hranijo. V ta namen uporabljamo pripravke, ki polže izsušujejo in povzročajo močno izločanje sluzi (Prior, 1985). Ker se z izločanjem sluzi polži v kritičnih razmerah zaščitijo le enkrat, mora biti takšna ovira dovolj široka.…”
Section: Zatiranjeunclassified